a. 5(x+4) + 2(x+3)
b. 3(y+6) + 4(y-5)â
Answer:
Step-by-step explanation:
a. 5(x+4) + 2(x+3) = 5*x + 5*4 + 2*x + 2*3
= 5x + 20 + 2x + 6
= 5x + 2x + 20 +6 {bring like terms together}
= 7x + 26
b. 3(y+6) + 4(y-5)â = 3*y + 3*6 + 4*y - 4*5
= 3y + 18 + 4y - 20
= 3y + 4y + 18 - 20 {bring like terms together}
= 7y - 2
Answer:
a. 7x+26
b.7y-2
Step-by-step explanation:
for question a
1.Do 5 multiplied by x (5x) and 5 multiplied by 4 (20) and do the same with the other brackets
2. simplify the expression (collect the like terms)
5x+20+2x+6=6x+26
3.calculate the sum
DO THE SAME FOR QUESTION b
Answer:
29
Step-by-step explanation:
anythin0.5 or higher you round up so for 28.5 you round up to 29.
hope this helps. :)
Answer:
29
Step-by-step explanation:
When its .5 - .9 you round up and when its .1 - .4 you round down
Answer:
26 Centimeters
Step-by-step explanation: